A dual-functional heterogeneous ruthenium catalyst for the green one-pot synthesis of biphenols. Issue 15 (10th July 2017) - Maeno, Zen; Mitsudome, Takato; Mizugaki, Tomoo; Jitsukawa, Koichiro
Abstract : A green one-pot synthesis of biphenols using O2 and H2 was achieved using a magadiite-supported Ru nanoparticle catalyst. Abstract : A green one-pot synthesis of biphenols using O2 and H2 was achieved using a magadiite-supported Ru nanoparticle catalyst. This catalyst selectively promoted the oxidative coupling of phenols to diphenoquinones with O2, followed by the successive reduction of these diphenoquinones to biphenols using H2 in a single reactor.